Experimental assessment of hydrodynamic behavior in a gravitational vortex turbine with different inlet channel and discharge basin configurations (2024)
Gravitational vortex turbines can provide a sustainable and efficient solution for generating renewable energy from small watercourses, minimizing environmental impact, and contributing to the decentralization of energy production. Their design allows for high energy efficiency even under low flow conditions, thus benefiting rural communities and reducing their dependence on fossil fuels. This paper presents an experimental assessment of the hydrodynamic behavior of gravitational vortex turbines by examining various geometric configurations. The combinations of two types of inlet channels (spiral and tangential) and two types of discharge basins (conical and cylindrical) were investigated. Additionally, different geometries and placements of the runners were evaluated to determine their influence on the efficiency and performance of the turbine. The results indicate that the highest efficiency of 60.85% was achieved with a configuration that included a spiral inlet channel, cylindrical discharge, and a runner placement of 50%.